2012
DOI: 10.1016/j.gca.2011.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium isotope fractionation during hydrous magnesium carbonate precipitation with and without cyanobacteria

Abstract: How to cite:Mavromatis, Vasileios; Pearce, Christopher R.; Shirokova, Liudmila S.; Bundeleva, Irina A.; Pokrovsky, Oleg S.; Benezeth, Pascale and Oelkers, Eric H. (2012) AbstractThe hydrous magnesium carbonates, nesquehonite (MgCO 3 Á3H 2 O) and dypingite (Mg 5 (CO 3 ) 4 (OH) 2 Á5(H 2 O)), were precipitated at 25°C in batch reactors from aqueous solutions containing 0.05 M NaHCO 3 and 0.025 M MgCl 2 and in the presence and absence of live photosynthesizing Gloeocapsa sp. cyanobacteria. Experiments were perfor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
71
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 97 publications
(84 citation statements)
references
References 48 publications
10
71
1
Order By: Relevance
“…The reproducibility of δ 26 Mg measurements for the liquid Mg standards DSM3, CAM1, and OUMg and the dolomite carbonate standard JDo-1 used during this study was better than 0.02‰, 0.08‰, 0.09‰ and 0.10‰, respectively. This precision is similar to that reported earlier from our laboratory Beinlich et al, 2014;Mavromatis et al, 2012Mavromatis et al, , 2013Mavromatis et al, , 2014aMavromatis et al, , 2014bShirokova et al, 2013), and fall within the previously reported values for these standards reported by other groups (Li et al, 2012(Li et al, , 2014Tipper et al, 2006;Bolou-Bi et al, 2009;Geske et al, 2015;Immenhauser et al, 2010;Pogge von Strandmann, 2008;Wombacher et al, 2009Wombacher et al, , 2011.…”
Section: Mg Isotope Analysessupporting
confidence: 92%
See 3 more Smart Citations
“…The reproducibility of δ 26 Mg measurements for the liquid Mg standards DSM3, CAM1, and OUMg and the dolomite carbonate standard JDo-1 used during this study was better than 0.02‰, 0.08‰, 0.09‰ and 0.10‰, respectively. This precision is similar to that reported earlier from our laboratory Beinlich et al, 2014;Mavromatis et al, 2012Mavromatis et al, , 2013Mavromatis et al, , 2014aMavromatis et al, , 2014bShirokova et al, 2013), and fall within the previously reported values for these standards reported by other groups (Li et al, 2012(Li et al, , 2014Tipper et al, 2006;Bolou-Bi et al, 2009;Geske et al, 2015;Immenhauser et al, 2010;Pogge von Strandmann, 2008;Wombacher et al, 2009Wombacher et al, , 2011.…”
Section: Mg Isotope Analysessupporting
confidence: 92%
“…cyanobacteria. As emphasized by Mavromatis et al (2012), Gloeocapsa sp. does not affect the extent of Mg isotope fractionation between hydrous Mg carbonates and the aqueous solution.…”
Section: Theoretical Versus Experimental Mg Isotope Fractionation Andmentioning
confidence: 91%
See 2 more Smart Citations
“…Black et al, 2008;Bolou-Bi et al, 2010;Li et al, 2010;Wimpenny et al, 2010;Opfergelt et al, 2012Opfergelt et al, , 2014Pogge von Strandmann et al, 2008;Shirokova et al, 2013;Teng et al, 2010;Tipper et al, 2010;Hwang et al, 2012;Ilina et al, 2103;Mavromatis et al, 2012Mavromatis et al, , 2014. Such processes could lead to global riverine fluxes that are isotopically lighter in Mg compared to the homogenous chondritic composition of the Earth's mantle (Tipper et al, 2006).…”
Section: Introductionmentioning
confidence: 99%